Analyzing the role of industrial sector's electricity consumption, prices, and GDP: A modified empirical evidence from Pakistan - Kashif Raza Abbasi; Khadim Hussain; Jaffar Abbas; Festus Fatai Adedoyin; Pervez Ahmed Shaikh; Hazrat Yousaf; Faqeer Muhammad (AIMS Energy, 2021)
Electricity usage plays a vital role in raising the massive growth in the economy; also, the industrial sector is the key factor of overall energy demand closely related to the economy. The study aims to contribute in two ways. First, the Vector Error Correction Model (VECM) estimates electricity consumption in Pakistan during 1970-2018 to find the relationship between electricity consumption, price, and real gross domestic product. Second, decomposing the overall impact of an unexpected shock on each variableos Dynamic Variance Decomposition Technique applied. The empirical analysis shows that the factors are co-integrated. The results also indicate the long-run relationship between electricity consumption, price, and real gross domestic product in the industrial sector. Further, the VECM analysis responses are also confirmed by the variance decomposition method. The findings confirm the potential of the industrial sector. We propose that formalized and proper assurance of electricity needs and demands at a reasonable price can boost the local industry's confidence and attract foreign investors. However, a strong governance structure should be extended to the public sector to ensure policies that priorities the distribution of energy to businesses for development.